2021
DOI: 10.1038/s41419-021-03810-9
|View full text |Cite
|
Sign up to set email alerts
|

Pericentromeric Satellite III transcripts induce etoposide resistance

Abstract: Non-coding RNA from pericentromeric satellite repeats are involved in stress-dependent splicing processes, maintenance of heterochromatin, and are required to protect genome stability. Here we show that the long non-coding satellite III RNA (SatIII) generates resistance against the topoisomerase IIa (TOP2A) inhibitor etoposide in lung cancer. Because heat shock conditions (HS) protect cells against the toxicity of etoposide, and SatIII is significantly induced under HS, we hypothesized that the protective effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…It was noticed that heat stress (HS) conditions protect cells against the toxicity of chemotherapeutic drugs, most prominently the topoisomerase 2 (TOP2) inhibitor etoposide [ 117 ]. Recent results show that in response to heat stress, human satellite III RNA recruits topoisomerase IIa (TOP2A) to nuclear stress bodies and generates resistance against the TOP2A inhibitor etoposide in lung cancer [ 118 ]. Etoposide is frequently used to treat lung cancer and it temporarily stabilizes transiently induced DNA double-stranded breaks (DSB) created by TOP2A.…”
Section: Satellite Dna In Oncogenic Transformationmentioning
confidence: 99%
See 2 more Smart Citations
“…It was noticed that heat stress (HS) conditions protect cells against the toxicity of chemotherapeutic drugs, most prominently the topoisomerase 2 (TOP2) inhibitor etoposide [ 117 ]. Recent results show that in response to heat stress, human satellite III RNA recruits topoisomerase IIa (TOP2A) to nuclear stress bodies and generates resistance against the TOP2A inhibitor etoposide in lung cancer [ 118 ]. Etoposide is frequently used to treat lung cancer and it temporarily stabilizes transiently induced DNA double-stranded breaks (DSB) created by TOP2A.…”
Section: Satellite Dna In Oncogenic Transformationmentioning
confidence: 99%
“…The inability of TOP2A to form a complex with etoposide results in decreased DNA damage after treatment that impacts downstream DNA repair pathways. Etoposide resistance can be overcome by inhibiting human satellite III expression with epigenetic regulator BRD4 inhibitors [ 118 ]. The results show potential roles of satellite RNAs in cancer therapy resistance and suggest the therapeutic relevance of human satellite III RNA.…”
Section: Satellite Dna In Oncogenic Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, TOP2A is mainly distributed in the nucleus and participates in the cell cycle pathway, which is closely related to cell proliferation and apoptosis ( Tian et al, 2021 ). By analyzing the effect of the expression level of TOP2A protein on the proliferation and invasion of tumor cells, the researchers found that the expression of TOP2A protein was closely related to the proliferation and invasion of LC cells ( Kanne et al, 2021 ). However, there are few studies on TOP2A in the nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Early evidence showed that several genotoxic agents cause overexpression of centromeric repeats in non-cancerous murine cells ( Hedouin et al, 2017 ). Further study in humans demonstrated satellite III repeat hypomethylation in cancerous compared to normal tissue, which was associated with etoposide resistance in non-small cell lung carcinoma ( Kanne et al, 2021 ). The authors also showed that etoposide resistance is accomplished by sequestering topoisomerase 2A (TOP2A) in nuclear stress bodies.…”
Section: Introductionmentioning
confidence: 99%